FENOMENA PERGESERAN NILAI–NILAI RELIGIUS MAHASISWA PAI UIN MALANG AKIBAT KOREAN WAVE (K-POP DAN K-DRAMA) - Zakiyah Z, Afaf; Rifqi, Naflah; Zaituni, Rohmatul Azizah (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
K-Pop and K-Drama, which were allegedly only dimensioned in the entertainment world, turned out to have implications for the religiosity of the audience. It has been proven that some acts of fanaticism shown by the fans resulted in the level of faith and the intensity of their worship decreasing. The spread of the Korean Wave (hallyu) which includes K-Pop and K-Drama is well packaged and visualized based on international standards, so that various demographic layers -including Islamic Religious Education students- can access it easily and at the same time enjoy it. With the increasing number of fans, the imperialism of the Korean Wave which is rooted in K-Pop and K-Drama has become a new wave of globalization The shift that arises is not only in the cultural aspect, a significant shift in religiosity is also rife. This study aims to determine the phenomenon of shifting religious values ​​due to the Korean Wave, especially K-Pop and K-Drama. This research uses an interview method with a qualitative descriptive approach. Subjects are students of Islamic Religious Education at the State Islamic University of Malang with an age category of 18 to 21 years. The results of this study showed that the subjects experience symptoms of decreased religiosity, including the intensity of studying religion is distracted by the intensity of enjoying Korean content, delaying prayers because watching idol concerts and K-Dramas, deepening the history of idols or Korean culture compared to Islamic Tarikh science, and also memorizing Korean songs more than Islamic songs. Some respondents even stated that they are more interested in learning Korean than Arabic. This phenomenon is a challenge for the world of Islamic education. However, this needs to be analyzed further in order to take lessons in Islamic da'wah both in the internal (Muslims) and external spheres. Abstrak K-Pop dan K-Drama yang disinyalir hanya berdimensi pada dunia hiburan ternyata telah mengimplikasi religiusitas para penikmatnya. Telah terbukti beberapa tindak fanatisme yang ditampakkan oleh para fans mengakibatkan kadar keimanan dan intensitas ibadah mereka menurun. Persebaran Korean Wave (hallyu) yang termasuk di dalamnya K-Pop dan K-Drama dikemas dengan apik dan divisualisasikan berdasar standar internasional, sehingga berbagai lapisan demografi -tak terkecuali mahasiswa Pendidikan Agama Islam- dapat mengaksesnya dengan mudah juga sekaligus menggemarinya. Pergeseran yang timbul tak hanya pada aspek budaya, pergeseran religiusitas yang signifikan juga marak terjadi. Penelitian ini bertujuan untuk mengetahui fenomena pergeseran nilai-nilai religius akibat Korean Wave, khususnya K-Pop dan K-Drama. Penelitian ini menggunakan metode wawancara dengan pendekatan deskriptif kualitatif. Subjek adalah mahasiswa Pendidikan Agama Islam Universitas Islam Negeri Malang dengan kategori usia 18 sampai 21 tahun. Hasil penelitian ini menunjukkan bahwa subjek mengalami gejala penurunan religiusitas, di antaranya intensitas mengkaji agama teralihkan dengan intensitas menikmati konten Korea, menunda sholat karena menonton konser idola dan K-Drama, lebih mendalami sejarah idola atau kebudayaan Korea dibanding dengan ilmu Tarikh Islam, lebih menghafal lagu-lagu Korea daripada lagu-lagu Islami, dan juga lebih tertarik belajar bahasa Korea dibanding bahasa Arab. Fenomena yang terjadi merupakan tantangan bagi dunia pendidikan Islam. Bagaimanapun hal ini perlu dianalisis lebih lanjut guna mengambil hikmah dalam dakwah Islam baik di lingkup internal (kaum muslimin) maupun lingkup eksternal.